A retrospective audit of young patients diagnosed with cervical cancer over ten years at Groote Schuur Hospital, Cape Town between 1 January 2003 and 31 December 2012, and their outcome at five-year follow-up compared to women in the prior decade - Govindasamy, Suveshni (Department of Obstetrics and Gynaecology, 2020)
Background : Cervical cancer is the second commonest gynaecological cancer amongst women worldwide and the leading cause of cancer deaths in developing countries – contributing 83% of new cases and 85% of all deaths annually to the burden of this disease. Information and awareness of this illness in the developing world is still inferior, and mortality is increasing. In the developing world, late presentation, advanced-stage disease and a poorly run screening programme (covering only 55% of the South African population) are all contributing factors to this statistic. Approximately 20% of all South African women in their reproductive age are also HIV positive. With the rising burden of cervical cancer and the emergence of HIV as an influencing comorbidity, South Africa adopted a national cervical screening programme, rolled out in 2000 as well as an HCT (HIV counselling and testing) programme formalised in 2011. With these initiatives now in place, this study examined trends and compared 5-year survival outcomes between two decades for cervical cancer among young women. Methods : The study undertook a retrospective audit of files and information on the pre-existing cervical cancer database, and appropriate data was extracted (HREC REF 344/2011). Survival and disease outcomes at five years, as well as time to recurrence, was assessed, together with other demographics of the study population. Patients included in the study were non-pregnant female patients, aged 40 years and younger at the time of registration with the Groote Schuur Hospital (GSH) Oncology Unit (LE 33). The diagnosis of cervical cancer had to have been confirmed histologically, as either squamous cell carcinoma or adenosquamous carcinoma or adenocarcinoma. Patients must have attended at the LE 33 unit on or from 1 January 1993 until and including 31 December 2012. The two decades were studied and 5-year outcomes from each decade were analysed and reviewed using Kaplan-Meier curves and univariate analyses. The study compared data using Log Rank tests and p-values. Findings : The two decade-groups under study showed no difference in trends of survival regarding age, treatment type and histology. Albeit small numbers, adenocarcinoma was the histology that had the best probability of survival during both decades. There were more patients with early-stage cancer (stage 1 and 2) diagnosed in decade B (2003 – 2012) than A (1993 – 2002). Within this early-stage cervical cancer cohort, there is a trend toward more locally-advanced (stage 2) cancer in the more recent decade. The proportion of patients presenting with stage 1a and 1b cancer with tumours 4 cm and less has halved from decade A to decade B. The proportion of stage 2 cancers presenting with tumours 2 – 4cm in size during decade B has risen almost 3-fold to that of decade A. This suggests a developing trend of presentation of more locally-advanced cancer. During both decades, stage 1 cervical cancers had the best probability of survival, with an improvement in mean survival from decade A (average of 44 months) to decade B (average of 58 months). The trend of stage 2 disease has deteriorated, with a decrease in mean survival (from 48 months in decade A to 21 months in decade B), an increase in cancer-related deaths and a shorter time to relapse. The number of patients presenting with late-stage disease (stages 3 and 4) has declined. HIV positive status played an influential role in tumour size on presentation and probability of 5-year disease-free survival. Young women who were HIV positive also fared less favourably when compared to NP (not positive) women in terms of mean survival. Due to the small sample size and that the majority of patients in decade A were untested, further HIV comparisons were not credible. Interpretation : The study suggests a moving trend towards young patients that are being diagnosed with the more locally-advanced early-stage disease in the more recent decade than ten years prior. HIV status seemingly played an influential comorbid role in patients diagnosed with cervical cancer. Patients with the locallyadvanced disease appear to have worse outcomes in the latter decade. In an attempt to curb this potentially curable disease in this subset of young women, a greater focus on earlier screening interventions, prompt diagnosis and appropriate and timeous treatment of cervical cancer, together with optimisation of comorbidities like HIV are needed.